Factors associated with persistent urinary incontinence - DEVORE, Elizabeth E. (2013)
OBJECTIVE: Many women with urinary incontinence (UI) have symptoms that continue over many years; however, virtually nothing is known about factors that are associated with persistent UI. STUDY DESIGN: We studied 36,843 participants of the Nurses’ Health Study, aged 54–79 years at baseline for the UI study, who provided UI information on biennial questionnaires from 2000 to 2008; follow up in the Nurses’ Health Study is 90%. In total, 18,347 women had “persistent UI,” defined as urine leakage ≥1/month reported on all five biennial questionnaires during this eight-year period; 18,496 women had no UI during this period. Using multivariable-adjusted logistic regression, we estimated odds ratios (OR) of persistent UI versus no UI across various demographic, lifestyle, and health-related factors, which were derived from reports in 2000. RESULTS: Increasing age group, white race, greater parity, greater BMI, and lower physical activity levels were each associated with greater odds of persistent UI, as were several health-related factors (i.e., stroke, type 2 diabetes, and hysterectomy). Associations with persistent UI were particularly strong for increasing age group (p-trend<0.0001; OR=2.75, 95% CI=2.54–2.98 comparing women aged ≥75 vs. <60 years) and greater BMI (p-trend<0.0001; OR=3.14, 95% CI=2.95–3.33 comparing women with BMI ≥30 vs. <25 kg/m(2)); moreover, black women had much lower odds of persistent UI compared to white women (OR=0.27, 95% CI=0.21–0.34). CONCLUSIONS: Factors associated with persistent UI were generally consistent with those identified in previous studies of UI over shorter time periods; however, older age, white race, and obesity were particularly strongly related to persistent UI.